2014
DOI: 10.1016/j.febslet.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of bael quinolone synthase in tobacco improves plant vigor under favorable conditions, drought, or salt stress

Abstract: a b s t r a c tType III polyketide synthases (PKSs) catalyze the biosynthesis of various medicinally important secondary metabolites in plants, but their role in growth and stress response is unclear. Here, we overexpressed quinolone synthase (QNS) from bael in tobacco. QNS-overexpressing plants showed an overall increase in growth, photosynthetic efficiency and chlorophyll content compared to wild type plants. Second-generation (T 2 ) transgenic plants grew to maturity, flowered early and set viable seeds und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Gas exchange was measured with an open gas-exchange system (LI-6400, Li-Cor, Lincoln, NE, USA). Measurements of net photosynthetic rate (Pn), transpiration rate, and respiration rate were performed as previously described (Resmi et al 2015).…”
Section: Measurement Of Chlorophyll Content and Photosynthesismentioning
confidence: 99%
“…Gas exchange was measured with an open gas-exchange system (LI-6400, Li-Cor, Lincoln, NE, USA). Measurements of net photosynthetic rate (Pn), transpiration rate, and respiration rate were performed as previously described (Resmi et al 2015).…”
Section: Measurement Of Chlorophyll Content and Photosynthesismentioning
confidence: 99%
“…Overexpression in tobacco of a quinolone synthase gene, a participant in the flavonoid synthesis pathway, of bael increased the root length of the transgenic plants and improved drought tolerance (Resmi et al, 2015). In the present study, the growth of OE lines and WT tobacco seedlings under nature drought stress was evaluated (Figure 4A).…”
Section: Overexpression Of Cpchs1 Enhances Seed Germination In Drough...mentioning
confidence: 89%
“…With regard to the salt tolerance of Populus euphratica, genes associated with the flavonoid synthesis pathway are differentially expressed, illustrating the importance of flavonoidrelated genes in participating in stress responses to abiotic stress (Zhang et al, 2019). The improvement of plant tolerance to drought and salt stress is related to the increase of flavonoids, phenolics, and alkaloids (Resmi et al, 2015). Similarly, overexpression of CpCHS1 increased the germination frequency of tobacco under experimentally induced drought stress, possibly by increasing flavonoid or alkaloid biosynthesis (Gu et al, 2020;Yang et al, 2020).…”
Section: Overexpression Of Cpchs1 Enhances Seed Germination In Drough...mentioning
confidence: 99%
“…An increase in the degree of unsaturation of membrane lipids was associated with improved drought resistance and ROS neutralization (He and Ding, 2020a, Ullah et al, 2022, Zi et al, 2022), which highlights the potential role of fatty acid composition in poplar leaf palisade cells to help mitigate the L-WD stress-related consequences. Looking at leaf physiological parameters during WD stress (Supplementary Figure S1B), compared to E-WD, photosynthesis, leaf conductance, and transpiration rates were improved during L-WD, signifying the possible roles of flavonoids and fatty acids in neutralizing ROS (Jia et al, 2021, Resmi et al, 2015), leading to the observed improved leaf performance during L-WD stress.…”
Section: Discussionmentioning
confidence: 99%